\(\cfrac{by+cz}{b^2+c^2}=\cfrac{cz+ax}{c^2+a^2}=\cfrac{ax+by}{a^2+b^2}\)
\(=\cfrac{by+cz+cz+ax+ax+by}{b^2+c^2+c^2+a^2+a^2+b^2}\)
[সংযোজন প্রক্রিয়া করে পাই]
\(=\cfrac{2(ax+by+cz)}{2(a^2+b^2+c^2)}\)
\(=\cfrac{ax+by+cz}{a^2+b^2+c^2}\)
\(\therefore \cfrac{by+cz}{b^2+c^2}=\cfrac{ax+by+cz}{a^2+b^2+c^2}\)
বা, \((by+cz)(a^2+b^2+c^2)\)
\(=(b^2+c^2)(ax+by+cz)\)
বা, \(a^2(by+cz)+(b^2+c^2)(by+cz)\)
\(=ax(b^2+c^2)+(b^2+c^2)(by+cz)\)
বা, \(a^2(by+cz)=ax(b^2+c^2)\)
বা, \(\cfrac{by+cz}{b^2+c^2}=\cfrac{ax}{a^2}\)
বা, \(\cfrac{by+cz}{b^2+c^2}=\cfrac{x}{a}------(i)\)
আবার, \(\cfrac{cz+ax}{c^2+a^2}=\cfrac{ax+by+cz}{a^2+b^2+c^2}\)
বা, \((cz+ax)(a^2+b^2+c^2)\)
\(=(c^2+a^2)(ax+by+cz)\)
বা, \(b^2(cz+ax)+(c^2+a^2)(cz+ax)\)
\(=by(c^2+a^2)+(c^2+a^2)(cz+ax)\)
বা, \(b^2(cz+ax)=by(c^2+a^2)\)
বা, \(\cfrac{cz+ax}{c^2+a^2}=\cfrac{by}{b^2}\)
বা, \(\cfrac{cz+ax}{c^2+a^2}=\cfrac{y}{b}------(ii)\)
এবং, \(\cfrac{ax+by}{a^2+b^2}=\cfrac{ax+by+cz}{a^2+b^2+c^2}\)
বা, \((ax+by)(a^2+b^2+c^2)\)
\(=(a^2+b^2)(ax+by+cz)\)
বা, \(c^2(ax+by)+(a^2+b^2)(ax+by)\)
\(=cz(a^2+b^2)+(a^2+b^2)(ax+by)\)
বা, \(c^2(ax+by)=cz(a^2+b^2)\)
বা, \(\cfrac{ax+by}{a^2+b^2}=\cfrac{cz}{c^2}\)
বা, \(\cfrac{ax+by}{a^2+b^2}=\cfrac{z}{c}------(iii)\)
\((i), (ii)\) এবং \((iii)\) নং সমীকরন থেকে পাই, \(\cfrac{x}{a}=\cfrac{y}{b}=\cfrac{z}{c}\)(প্রমাণিত)